Malignant peripheral nerve sheath tumour over the posterior triangle of neck: a rare case report - Chavan, Shahaji; Bhatnagar, Shubhi P.; Bendre, Mahendra; Dnyanmote, Anuradha; Kshirsagar, Vinayak; Sinha, Nilesh; Thiyagarajan, Amrithraj (International Surgery Journal, 2017)
Malignant peripheral nerve sheath tumour (MPNST) is an extremely rare soft tissue sarcoma which usually arises from peripheral nerves or somatic soft tissue with an incidence of 0.001%. It’s most common anatomical sites are the proximal portions of the upper and lower extremities and the trunk and it’s extremely rare for such a tumour to occur elsewhere in the body. We report a rare case of such a tumour over the left posterior aspect of neck in a 28-year-old female patient. We have reviewed this case in terms of clinical presentation, investigations, surgical treatment and adjuvant therapy and have shortly described our experience. MRI and CT neck supported the diagnosis of this tumour. Fine needle aspiration cytology taken from the swelling revealed a low-grade spindle cell tumour with a possibility of MPNST. Excision of the tumour was done and the excised specimen was sent for histopathological examination which revealed MPNST. Adjuvant radiotherapy was given postoperatively. At a 6-month follow-up, patient is doing well with no evidence of recurrence. Suspicion of this tumour should be raised in a rapidly growing painless tumour in and around a nerve tissue. Diagnosis is made by assessing a combination of clinical, pathological and immunohistochemistry features. Complete surgical removal should be the goal of treatment with definitive histological diagnosis. A regular follow up is recommended to confirm any recurrence or metastasis.